(untitled) (Brazilian Journal of Pharmaceutical Sciences, 2019)
Anesthetics are an indispensable prerequisite for surgical intervention and pharmacological animal studies. The objective of present study was to optimize the dose of ketamine (K) and xylazine (X) along with atropine sulfate (A) in order to achieve surgical tolerance in BALB/c mice. Several doses of ketamine (100, 150, 200 mg/kg) and xylazine (10, 15, 20 mg/kg) were mixed and combination of nine doses (K/X: 100/10, 100/15, 100/20, 150/10, 150/15, 150/20, 200/10,200/15,200/20) were evaluated (n=9 per combination). A constant dose of atropine (0.05 mg/kg) was also used to counter side effect. Timerelated parameters were evaluated on the basis of reflexes. KX at dose 200/20 mg/kg produced surgical tolerance in all nine mice with duration 55.00±6.87 minutes. The induction time 0.97±0.09 minutes, sleeping time 90.67±5.81 minutes and immobilization time (102.23±6.83 minutes) were significantly higher than all combination. However, this combination was considered unsafe due to 11 % mortality. While, KX at dose 200/15 mg/kg results in none of the mortality, so was considered as safe. Moreover, this combination produces surgical tolerance in 89 % mice with duration (30.00±7.45 minutes). It was concluded that KX at dose 200/15 mg/kg along with atropine 0.05 mg/kg is safe for performing surgical interventions in BALB/c mice.